Sosialisasi Pelayanan Prima di Rumah Sakit Ibu dan Anak Fadhila Batusangkar - Nindi Riyan Gustin; Zakaria Habib Al-Razie; Nida Silvia Lestari; Muhamad Iqbal Al-Mas’ud; Mimah Rohimah (Lembaga Pengembangan Kinerja Dosen, 2026)
Fadhila Maternal and Child Hospital in Batusangkar faces three problems in public service delivery, namely the absence of uniform service excellence standards, the lack of written standard operating procedures on service behavior, and an organizational culture not yet oriented toward patient satisfaction. These problems stem from limited knowledge among management staff. This community service activity aims to improve the knowledge, attitudes, and commitment of management staff in applying service excellence. The activity used interactive lectures, group discussions, case simulations, and structured reflection for 20 management staff. Effectiveness was measured through pre-test and post-test scores and the Wilcoxon Signed-Rank Test. Results show the average knowledge score rose from 57.4 to 81.3, an increase of 41.6 percent. As many as 90 percent of participants reached the good and very good categories. The statistical test produced a p value below 0.001, indicating a significant improvement. The largest gain occurred in mastery of the A6 principles at 51.9 percent, and participant satisfaction reached 94.5 percent. The activity produced follow-up commitments and a recommendation document for developing service excellence standard operating procedures for the hospital.